RecA K72R Filament Formation Defects Reveal an Oligomeric RecA Species Involved in Filament Extension - Britt, Rachel L. (American Society for Biochemistry and Molecular Biology, 2011)
Using an ensemble approach, we demonstrate that an oligomeric RecA species is required for the extension phase of RecA filament formation. The RecA K72R mutant protein can bind but not hydrolyze ATP or dATP. When mixed with other RecA variants, RecA K72R causes a drop in the rate of ATP hydrolysis and has been used to study disassembly of hydrolysis-proficient RecA protein filaments. RecA K72R filaments do not form in the presence of ATP but do so when dATP is provided. We demonstrate that in the presence of ATP, RecA K72R is defective for extension of RecA filaments on DNA. This defect is partially rescued when the mutant protein is mixed with sufficient levels of wild type RecA protein. Functional extension complexes form most readily when wild type RecA is in excess of RecA K72R. Thus, RecA K72R inhibits hydrolysis-proficient RecA proteins by interacting with them in solution and preventing the extension phase of filament assembly.